Digital marketing in online shopping / Baderisang Mohamed and Aimy Zatul Akhmar Muhamad Nor Azeri - Mohamed, Baderisang; Muhamad Nor Azeri, Aimy Zatul Akhmar (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Digital marketing is the usage combination of mobile devices, social media, search engines, internet and other channels to reach the audiences. It is a new way in understanding how customers behave and approaching them compared to traditional marketing (Barone, 2020). However, online shopping is purchasing goods and services over the internet through the use of web browser (Hope, 2020). Consumers can find literally anything that they need without even leaving the house. There are many online platforms for people to shop with, which are widely used in Malaysia such as Shopee, Lazada and PG Mall (Department, 2020). Almost anything can be purchased online today; the e-commerce websites are amounting approximately billion a year in sales.